Characteristics of a successful collaboration in evaluation of a health care innovation: lessons learned from GPS locator technology for dementia clients (2017)
Becoming lost or its risk is a problem for dementia clients, their families and caregivers. The purpose of the paper is to describe, analyze and share lessons from a pilot project to use global positioning system devices to manage the risk of becoming lost and, at the same time, maintaining client autonomy. The study informs technology implementation approaches and strategies for innovative health technologies. The project used a prospective mixed-methods approach including a pre and post paper-based questionnaire, focus groups and individual interviews. Technology uptake was examined post knowledge transfer using the After Action Review method, which has shown utility in military and health care settings. Project successes and weaknesses are identified to inform future approaches of innovative health technology pilot projects. Lessons from the pilot emphasize the need for innovators to understand the multifaceted context they are entering, enlist the support of leaders, dedicate a project lead, support autonomous decision making and problem solving, meet regularly to monitor progress and address issues and support peer-to-peer collaboration.